UKRAINIAN LANGUAGE AND HISTORICAL PARALLELS IN THE CONTEXT OF 2022-2023 - Lakhtionova , Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of the language situation in Ukraine in the 2022-2023. It is analyzed how the perception of the native language by a Ukrainian has changed. The events of the last two years fundamentally influenced the vision of Ukrainian and Russian languages by Ukrainian society. These changes are proven by some historical facts that happened in Europe and Central Asia. Such factors as war invasion, the influence of the policy of totalitarian regimes, especially the influence of language and cultural politics upon the language situation, national mentality, and conscience of the Ukrainian nation are considered. The forecast of the future language situation in Ukraine is presented, for the historical empirical experience may suggest some repeating regularities. It is all proved by historical facts, cultural, and artistic events, sociolinguistic conditions, studies, and the opinions of Ukrainian and foreign scientific authorities and influencers quoted. __________ References: • Baurіng, Bіll. «Movna polіtika v Ukraїnі: mіzhnarodnі normi ta zobov’jazannja і ukraїns’kij zakon ta zakonodavstvo.» Movna polіtika ta movna situacіja v Ukraїnі (Kiїv, Vidavnichij dіm “Kiєvo-Mogiljans’ka akademіja”, 2010): 55-95. • Kubajchuk, Vіktor. Hronologіja movnih podіj v Ukraїnі: zovnіshnja іstorіja ukraїns’koї movi (Kiїv, K.І.S, 2004), 178 • Masenko, Larisa. «Movna situacіja Ukraїni: socіolіngvіstichnij analіz.» Movna polіtika ta movna situacіja v Ukraїnі. Analіz і rekomendacії, 2-ge vidannja (Kiїv, Vidavnichij dіm “Kiєvo-Mogiljans’ka akademіja”, 2010): 96-131. • Movna polіtika ta movna situacіja v Ukraїnі. Analіz і rekomendacії, 2-ge vidannja (Kiїv, Vidavnichij dіm “Kiєvo-Mogiljans’ka akademіja”, 2010), 363. • Selezn’ov, Volodimir. Movnі vіjni. Mіf pro “zіpsovanіst’” ukraїns’koї movi (Harkіv: Vivat, 2019), 256. • Renchka, Іnna. Leksikon totalіtarizmu (Kiїv: Klіo, 2018), 232. • Devoto, Giacomo. Il linguaggio d’Italia. Storia e strutture linguistiche italiane dalla Preistoria ai nostri giorni (Milano: Rizzoli, 1995), 406. • Migliorini, Bruno. Storia della lingua italiana (Firenze: Sansoni, 1992), 761.